Photon-Counting Underwater Wireless Optical Communication by Recovering Clock and Data From Discrete Single Photon Pulses - Qiurong Yan; Zihang Li; Zhu Hong; Ting Zhan; Yuhao Wang (IEEE Photonics Journal, 2019)
To realize a long-distance underwater communication by using low-cost light emitting diode (LED) and single photon avalanche diode (SPAD), we proposed a method for recovering clock and data directly from discrete random pulse sequences output by SPAD. On this basis, a new communication model is established, taking into account not only fluctuations in photon flux and quantum efficiency of photon detection in a time-slot, but also the phase difference of the recovered clock caused by it. A photon-counting underwater optical wireless communication (UOWC) system was built. The effects of the system setting parameters such as the number of gating signals, synchronous character length and baud rate on the average bit error rate (BER) were verified by experiments. The experimental results show that under condition of only average 10 photons in one time-slot, photon-counting UOWC with a BER of 3.51 × 10−4 and a baud rate of 1 Mbps can be achieved.